Deinking and Bleacidng of Old Newsprint - Srivastava, Anita; Bhandari, K. S. (Indian Forester, 2000)
Old newsprint were deinked using sodium salts of benzene sulphonic acid (2.00%) and Nirma, a commercial detergent (2.00%) available in open market at the rate of Rs. 18 per kg, alone and with the addition of sodium hydroxide (1.50%) or sodium carbonate (1.50%), separately. Each pulp was bleached using mono stage calcium hypochlorite. Unbleached and bleached pulp field and brightness of the pulps were almost comparable, except marginally higher pulp yield for newsprint deinked with sodium salt of benzene sulphonic acid or commercial detergent, alone. Bleaching of pulps revealed that the highest brightness could be achieved in case of detergent and sodium carbonate deinked pulp, thus the pulp was also bleached by P and H/P bleaching sequence(s). It was observed that P stage bleached pulp possessed better strength properties and higher brightness than pulp bleached using other two bleaching sequences. On blending the pulp with bleached bamboo pulp in different ratio, the strength properties and brightness of the resulting pulp furnish improved consistently, hence a particular blending ratio may be chosen to make a paper of adequate properties desired for the end use.